Nontraditional Fragment Couplings of Alcohols and Carboxylic Acids: C(sp3)-C(sp3) Cross-Coupling via Radical Sorting - Sakai, Holt A.; MacMillan, David W. C. (Journal of the American Chemical Society, 2022)
Alcohols and carboxylic acids are among the most commercially abundant, synthetically versatile, and operationallyconvenient functional groups in organic chemistry. Under visible light photoredox catalysis, these native synthetic handles readilyundergo radical activation, and the resulting open-shell intermediates can subsequently participate in transition metal catalysis. Inthis report, we describe the C(sp3)-C(sp3) cross-coupling of alcohols and carboxylic acids through the dual combination ofN-heterocyclic carbene (NHC)-mediated deoxygenation and hypervalent iodine-mediated decarboxylation. This mild and practical Ni-catalyzed radical-coupling protocol was employed to prepare a wide array of alkyl-alkyl cross-coupled products, including highlycongested quaternary carbon centers from the corresponding tertiary alcohols or tertiary carboxylic acids. We demonstrate thesynthetic applications of this methodology to alcoholC1-alkylation and formal homologation, as well as to the late-stagefunctionalization of drugs, natural products, and biomolecules.